2010
DOI: 10.1007/s00192-010-1255-5
|View full text |Cite
|
Sign up to set email alerts
|

Intrasphincteric injections of autologous muscular cells in women with refractory stress urinary incontinence: a prospective study

Abstract: Cell therapy for severe multioperated cases of SUI is a mini-invasive, feasible, and safe procedure that can improve urinary condition in as a second line therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 21 publications
4
79
0
Order By: Relevance
“…However, the efficacy results differ widely, as the methodology used for studies was very different, as described below. All studies were phase II prospective observational studies, except for 2 randomized studies [1,2], in which patients were randomized to different doses of stem cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the efficacy results differ widely, as the methodology used for studies was very different, as described below. All studies were phase II prospective observational studies, except for 2 randomized studies [1,2], in which patients were randomized to different doses of stem cells.…”
Section: Resultsmentioning
confidence: 99%
“…All studies excluded urge incontinence or abnormal detrusor activity except for the study by Lee [5], which included 9 patients with mixed UI. However, in SUI, some only required that the patient had stress urinary incontinence (regardless of severity) [2,5,7,8] whereas others include only patients with SUI due to inherent sphincter weakness or at least exclude patients with urethral hypermobility > 45⁰ [1,3,9,10]. Nonetheless, it appears that the purpose of stem cells is to regenerate damaged sphincters, rather than to provide urethral support; in fact, some studies exclude patients with prolapse [2,4,9].…”
Section: Inclusion Criteria Of Patients In Studies For the Treatment mentioning
confidence: 99%
“…So far, the cells used for injection in human studies have been autologous myoblasts with or without fibroblasts, muscle-derived stem cells, muscle-derived cells, and umbilical cord blood stem cells [79]. The reported success rates are 50-100%, although followup is short-term and less than 1 year [80][81][82]. A recent study of 12 women with severe SUI with fixed urethra and previous failed surgery showed that intrasphincteric injections of autologous progenitor muscular cells isolated from a biopsy of the deltoid muscle are feasible and safe as a second-line treatment [81].…”
Section: Cell-based Therapymentioning
confidence: 99%
“…The reported success rates are 50-100%, although followup is short-term and less than 1 year [80][81][82]. A recent study of 12 women with severe SUI with fixed urethra and previous failed surgery showed that intrasphincteric injections of autologous progenitor muscular cells isolated from a biopsy of the deltoid muscle are feasible and safe as a second-line treatment [81]. In this study, 3 of 12 patients were dry at 12 months, 7 other patients were improved on pad test but not on voiding diary, and 2 patients were slightly worsened by the procedure.…”
Section: Cell-based Therapymentioning
confidence: 99%
“…(Mitterberger et al 2008;Sebe et al 2011) In the human studies, myoblasts and fibroblasts were obtained from muscle biopsies of the patient. Cells are then grown in a culture facility to yield more myoblasts.…”
Section: New Technologiesmentioning
confidence: 99%